The Role of Sustainable Accounting Practices in Guiding the Use of Artificial Intelligence to Enhance Social Responsibility in Banks: A Field Study on a Sample of Sudanese Banks (Sebha University Conference Proceedings, 2025)
This study aimed to explore the role of Artificial Intelligence (AI) through its key dimensions—intelligent automation, big data analytics, and predictive models—in enhancing social responsibility through sustainable accounting practices in Sudanese banks. The descriptive-analytical method was adopted, and a questionnaire was used to collect data from a sample of 131 accountants and auditors working in four banks: Agricultural Bank, Omdurman National Bank, Faisal Al-Sudani Bank, and Bank of Khartoum. The findings revealed a high level of awareness among employees of the importance of using AI in accounting operations, along with a strong commitment to applying sustainable accounting practices that support social responsibility, while also highlighting the need to improve collective accounting disclosure tools to strengthen transparency. The results also confirmed a statistically significant relationship and impact of AI, in all its dimensions, on social responsibility through sustainable accounting practices. The study recommends investing in training programs to build accountants’ and auditors’ AI-related skills, adopting more comprehensive and transparent disclosure policies, developing periodic reports to demonstrate banks’ contributions to social issues, and formulating an integrated strategy for AI adoption that ensures enhanced social responsibility and supports sustainable development.